Push-Out Bond Strength of Fiber-Reinforced Post Using Various Post Space Irrigation Treatments - Amir Mohammad Shahrokhi; Amir Ali Shahrokhi; Raoufeh Asghari; Mehdi Badiee; Kaveh Seyedan (Hindawi Limited, 2024)
Conclusion: The push-out bond strength values were significantly affected by the irrigation protocol. Using PUI and 17% EDTA + 5.25% NaOCl in apical region could be an effective irrigant for smear layer removal after post space preparation.